PEMBERDAYAAN MASYARAKAT MELALUI PENGENALAN PEMBIAYAAN SYARIAH DI DESA CIBUNIAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Muhamad Djedjen Syukrilah; Rully Trihantana; Ria Kusumaningrum (SAHID DEVELOPMENT JOURNAL, 2021)
Abstract This research is motivated because the Community Empowerment in the Economic Sector is not yet optimal by the Cibunian Village Government. the low level of the village government's ability to empower the community, as well as the low level of awareness of the village government towards the economic condition of the community. The research method used is descriptive qualitative. Data collection techniques used library research and field studies in the form of observations and interviews. The obstacles in economic empowerment are: (1) the limited budget for conducting training and limited knowledge from the village government (2) the lack of awareness of the people themselves who are reluctant to make comparisons to other regions, (3) the limited budget to be allocated as capital for the community members. business groups Efforts are being made to overcome these obstacles, namely: (1) designing and budgeting the village budget to be allocated to training business actors (2) providing understanding to the community, especially to business actors so that they can make comparisons to other regions in order to become an illustration of their business, (3) the village government seeks to find out the service or agency that handles making legality and immediately provides information to the community about how to make legality. Keywords: Community Empowerment, Economic Sector, Welfare and Creativity